(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
The barnacles included in the superfamily Coronuloidea are epizoic symbionts of various marine vertebrates (including cetaceans, sirenians, and sea turtles) and other crustaceans (crabs and horseshoe crabs). Among Coronuloidea, the so-called turtle barnacles (Chelonibiidae) are known from Paleogene times, whereas the whale barnacles (Coronulidae) likely appeared in the late Pliocene (Piacenzian). Although a derivation from the turtle barnacles (and especially from the genus Chelonibia) has been proposed, the evolutionary origin of Coronulidae remains to date obscure. In this work we reappraise a fossil record from upper Pliocene (Piacenzian) marine deposits at Casenuove (Empoli municipality, Tuscany, Italy) comprising various shells of Chelonibia testudinaria associated to a partial skeleton of a balaenid mysticete. Based on taphonomic and morpho-functional considerations, we discuss the hypothesis that the barnacles were hosted on the baleen whale, possibly on its callosities, which could have represented an analogous of the horny carapace of marine turtles. This record strongly suggests that the baleen whales can be added to the list of the possible hosts of the barnacles of the genus Chelonibia, thus hinting that the whale barnacles may have evolved from an ancient phase of dispersal of Chelonibia (or a similar ancestor) on mysticete cetaceans.